Implementation of Business Process Improvement (BPI) to Enhance Stock Opname and Purchasing Efficiency at XYZ Coffee - Nur Azizyah Putri Dewita; Adam Hermawan; Rangga Gelar Guntara (AI Society & STMIK Indonesia, 2025)
This study discusses the implementation of Business Process Improvement (BPI) through the adoption of a Point of Sale (POS) system and organizational restructuring to optimize stock-taking and purchasing processes at Soulja Coffee. The research employs the DMAIC (Define, Measure, Analyze, Improve, Control) approach to analyze and improve key business processes. The findings indicate that the purchasing process time decreased by up to 70%, from 4 hours 25 minutes – 5 hours 30 minutes to 1 hour 16 minutes – 2 hours 22 minutes per week. The Cost of Goods Sold (COGS) decreased from 54.9% in November to 38.2% in January, while Operating Expenses (OPEX) dropped from 34.6% to 16.4%, reflecting significant cost efficiency. The POS system enables real-time stock monitoring, reduces manual errors, and accelerates the procurement process. Organizational restructuring, including the establishment of a Finance & Purchasing division, shortened purchase approval times from 10 minutes to 3 minutes, improving responsiveness and transparency. Thus, the implementation of BPI at Soulja Coffee has proven effective in enhancing time efficiency, reducing operational costs, and supporting sustainable business growth.